A STUDY OF THE EFFECT OF HYPOTONIC HYPER-HYDRATION FLUIDS ON SODIUM BALANCE IN PAEDIATRIC HAEMATOLOGY/ONCOLOGY PATIENTS RECEIVING CHEMOTHERAPY. Issue 9 (17th August 2016) - Keane, Sinead; Butler, Eileen
Abstract : Aims: To determine the effect, if any, that hyper-hydration with hypotonic fluids has on sodium balance in paediatric haematology/oncology patients receiving cytotoxic chemotherapy treatment for malignancies. Methods: A literature review was carried out and a snapshot of current practice across paediatric haematology/oncology centres in the UK was obtained. A prospective study was carried out in a tertiary paediatric haematology/oncology centre. A total of 98 patient episodes involved hyper-hydration with isotonic 0.9% NaCl, almost isotonic 0.45% NaCl+2.5% glucose with added sodium bicarbonate or hypotonic 0.45% NaCl+2.5% glucose. Serum sodium was monitored before and during hyper-hydration. Results were analysed according to whether children experienced a drop in serum sodium. Results: Patients who were hyper-hydrated with hypotonic 0.45% NaCl & 2.5% Glucose experienced the greatest mean drop in serum sodium. The mean drop in sodium was 2.11 mmol/L in the group receiving the hypotonic 0.45% NaCl & 2.5% Glucose compared to 0.47 mmol/L in the group who received isotonic 0.9% NaCl or 0.45% NaCl & 2.5% Glucose with added sodium bicarbonate. During the course of the study five patients who received 0.45% NaCl & 2.5% Glucose dropped their sodium to 130 mmol/L or less constituting hyponatraemia. No patient dropped their serum sodium to 130 mmol/L or less in the other two groups. During the course of the study no patient experienced clinical manifestations of hyponatraemia. No child became hypernatraemic. Conclusions: In paediatric haematology/oncology patients receiving hyper-hydration with concurrent chemotherapy isotonic fluids are preferable.